Understanding cooperation from the experiences of Minang migrant women - Putri, Raniar Imania; Minza, Wenty Marina; Nurdiyanto, F. A. (Indigenous, 2022)
Abstract. Cooperation in the matrilineal Minang ethnic group is considered an essential element of their kinship system, especially cooperation with kins from the mother's side. With the increasing number of Minang women migrating to get a better education, this study aims to understand how cooperation is carried out by Minang migrant women and the realized form of cooperation. In-depth interviews were conducted with five Minang migrant women in Yogyakarta, as part of exploratory qualitative research, attempting to describe the migrant experience's participants. We found that the values taught are more inclined towards positive interdependence and effective action through coding analysis. Based on these positive idealizations, cooperation was generally achieved by mutual help (tolong-menolong) through equality matching, where there was a reciprocal relationship to achieve balance, which tends to occur at the level of the inter-group relations. We also found that cooperation tends to happen within the mother's family, parallel to the ideal of the Minang kinship system.Keywords: cooperation; migration; Minang; relation; women.